2022
DOI: 10.1186/s12912-022-00873-7
|View full text |Cite
|
Sign up to set email alerts
|

Family systems nursing conversations: influences on families with stroke

Abstract: Background Since a family member’s stroke affects the entire family, family systems nursing conversations (FSNCs) may be an appropriate intervention to support the family as a whole. The purpose of our study was to illuminate family members’ experiences within their family situations 6 months after participating in FSNCs when a family member under 65 years of age had suffered a stroke. Methods Fourteen semi-structured follow-up interviews were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“… 56 Each family member's productivity is impacted by the prevalence of chronic disorders like stroke and their subsequent effects. 57 Nursing care is essential for families dealing with the psychosocial effects of chronic disease. Therefore, it is of utmost importance to support the family members of individuals who have experienced a stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 Each family member's productivity is impacted by the prevalence of chronic disorders like stroke and their subsequent effects. 57 Nursing care is essential for families dealing with the psychosocial effects of chronic disease. Therefore, it is of utmost importance to support the family members of individuals who have experienced a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Penning and Wu showed that the burden of care was most significant for those who cared for their children and parents, respectively in Canada 56 . Each family member's productivity is impacted by the prevalence of chronic disorders like stroke and their subsequent effects 57 . Nursing care is essential for families dealing with the psychosocial effects of chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Por el contrario, representa una serie de intervenciones de Enfermería Familiar que se ofrecen en el contexto de conversaciones y vínculos entre enfermeros y familias, donde los primeros deben recurrir a sus habilidades terapéuticas y de comunicación (40) . Las conversaciones terapéuticas han aportado excelentes resultados a familias que atraviesan diversas situaciones de salud-enfermedad, como las que tienen niños diagnosticados con enfermedades crónicas (41) y adultos con insuficiencias cardíacas (42) o accidentes cerebrovasculares (43) , brindando mayor entendimiento mutuo y más cercanía entre familiares.…”
Section: Discussionunclassified
“…On the contrary, it configures a series of Family Nursing interventions offered in the context of a conversation and relationship between nurses and families, for which former must employ their therapeutic and communicational skills (40) . Therapeutic conversations have contributed great results for families experiencing diverse health-disease situations, such as those of children diagnosed with chronic diseases (41) and of adults with heart failure (42) or stroke (43) , promoting more mutual understanding and greater proximity among relatives.…”
Section: Discussionmentioning
confidence: 99%